Polysomnography Outcomes after Transoral Robotic Lingual Tonsillectomy for Obstructive Sleep Apnea. (2nd September 2014) - Smith, Chelsey; Argo, Jimmy L.; Jones, Kellie; Anderson, Michael; Vasan, Nilesh R.
Abstract : Objectives: Compare polysomnography (PSG) results before and after transoral robotic lingual tonsillectomy (TORLT) in patients with obstructive sleep apnea (OSA). Methods: Lingual tonsillar or base of tongue hypertrophy can be a cause of OSA but has proven difficult to address because of difficulty in accessing this area of the oropharynx through traditional surgical techniques. TORLT provides a simple, minimally invasive surgical technique for lingual tonsillectomy. Patients with OSA symptoms were assessed with preoperative PSG and sleep endoscopy for base of tongue obstruction. Selected candidates underwent TORLT followed by repeat PSG and nasal endoscopy after full recovery from the procedure. The pre‐ and postoperative PSG data were compared for each patient. Nonparametric comparisons were made using the signed rank test becasue of small sample size. Results: Ten patients underwent preoperative PSG and subsequent TORLT. Postoperative polysomnography data as available for 8 patients. Pre‐ and postoperative PSG comparisons (pre, post, P value) showed improvements in the median apnea‐hypopnea index (49.8, 19.5, P =. 84), sleep onset latency (11.8 minutes, 17.5 minutes, P =. 84), sleep efficiency (80.5%, 92.3%, P =. 2), and Epworth Sleepiness Scale (14.5, 10, P =. 88), but none were statistically significant. Conclusions: Transoral robotic lingual tonsillectomy improved polysomnography measures but not to a level of significance. This study is limited by small sample size and associated limited statistical power. Further study with larger sample sizes should be undertaken to more definitively study outcomes for this surgical technique.